Contestation Of Moderate And Radical Islam In Cyberspace - Hakiki, Kiki Muhamad; Badruzaman, Badruzaman; Rohmatika, Ratu Vina; Musofa, Ade (AL-ADYAN, 2024)
The internet has transformed the way millennials gain religious knowledge. Previously, they relied on print media like magazines, journals, or teachings from religious leaders. Today, they turn to convergence media that offers instant, though often incomplete, content. Islamic websites have become a primary source for quick religious information. This shift highlights new spaces on the internet for social interaction and religious discourse, particularly aimed at millennials. However, these digital spaces serve as more than just communication tools; they also act as channels for spreading religious messages, including propaganda and radicalism. Given the significance of Islamic websites as communication channels, studying radicalism on these platforms is essential. This is due to three key factors: first, Islamic websites have emerged as new communication platforms; second, religious messages online have a broad reach, crossing national borders; and third, internet-based information has a strong influence on users. This research is critical in preventing radicalism on websites and social media by uncovering the motivations behind the spread of radical messages online.